The Effect of Use of Red Dragon Leather Skin Extract and Long Storage to Water Content, Total Microby and Organoleptic Test Wet Noodle - Chairuni AR; Teungku Mia Rahmiyati; Zikrillah Zikrillah (Serambi Journal of Agricultural Technology, 2019)
Noodle products are generally used as an energy source because they have high enough carbohydrates. Wet noodles are raw noodles which before being marketed experience boiling process in boiling water, with water content around 35% and after boiling the water content increases to 52%. Relatively high water content results in a short shelf life and generally wet noodles have a shelf life of 36 hours at room temperature. Red dragon fruit skin contains high enough fiber and natural antioxidants namely β-carotene, as well as betasianin natural dyes. The antioxidant content of β-carotene in red dragon fruit skin which prolongs the shelf life of wet noodles, because antioxidants can protect cells from damage caused by unstable molecules known as free radicals. The purpose of this study was to determine the interaction of the effect of the use of red dragon fruit skin extract and storage time on moisture content, microbial total and organoleptic tests of wet noodles. The research method is by observing the water content, microbial total and organoleptic test of wet noodles. The results of this study are where the analysis of water content with an average of 55.24%. The results of microbial total analysis with an average of 1008,667 x 10 3. Whereas the results of the organoleptic analysis of the color of wet noodles with an average value of 3.90 (likes) and organoleptic tests of texture of wet noodles with an average value of 3.75 (likes).